The Teen Impact Experience: A Webcast Pilot Project for Teens With Cancer and Blood Diseases. (September 2014) - Gonzalez-Morkos, Betty; Zavala, Octavio; Malogolowkin, Marcio; Kuperberg, Aura
This article discusses a novel service, webcasting of a live group, implemented in response to the 2009-2010 H1N1 Flu pandemic by Teen Impact, a program geared at providing social therapy to adolescents diagnosed with cancer or a blood disorder. To ensure that services were not disrupted to adolescents on treatment despite flu restrictions, Teen Impact obtained necessary equipment to webcast the group. A total of 6 Teen Impact members participated in the webcast portion of the group. Findings revealed that existing members who had participated in the face-to-face Teen group were left with feelings of dissatisfaction due to lack of physical interaction with other members. New members appeared to enjoy this option admitting that the webcast provided them with the ability to feel supported by others with similar stories without having to face unknown members in person. A positive outcome from this type of intervention resulted in the webcast serving as a stepping stone for future face-to-face participation.